Exposure to pro-tobacco and anti-tobacco media messages and events and smoking behaviour among adolescents in Gambia - Isaac Yeboah Addo; Evelyn Acquah; Samuel H. Nyarko; Kwamena S. Dickson; Ebenezer N. K. Boateng; Castro Ayebeng (BMC, 2024)
Abstract Background Despite the widespread prevalence of adolescent smoking in Gambia, a West African country, there is limited research exploring the relationships between exposure to pro-tobacco and anti-tobacco media messages and events and smoking behaviour among young people. This study investigates the interplay of these exposures and smoking behaviour among 11-17-year-old adolescents in Gambia. Methods Secondary data analysis was conducted using the 2017 Gambia Global Youth and Tobacco Survey (GYTS), which included a total of 9,127 respondents. Descriptive and inferential analyses, including proportions, Pearson's chi-squared tests, and multivariable logistic regression models, were employed to estimate adjusted odds ratios (aOR) with 95% confidence intervals (CI). Results The final model revealed significant associations between exposure to anti-tobacco media messages and events and smoking behaviour. Adolescents exposed to anti-tobacco media messages had a 29% increased odds of smoking (aOR 1.29,CI = 1.08,1.53) compared to those unexposed, while exposure to anti-tobacco media events showed a 31% increased odds (aOR 1.31,CI = 1.09,1.59) compared to those unexposed. Exposure to pro-tobacco messages, such as witnessing tobacco use on TV (aOR 1.41, CI = 1.17,1.69) and owning objects with tobacco brand logos (aOR 1.49,CI = 1.19,1.86), was associated with higher odds of smoking. Covariates, including sex, age, and exposure to smoking behaviour by significant others, also demonstrated associations with smoking behaviour. Notably, male respondents showed significantly higher odds of smoking (aOR = 4.01,CI = 3.28,4.89) compared to females. Respondents aged 15 years and older had increased odds of smoking (aOR = 1.47,CI = 1.22,1.76) compared to those below 15 years old. Those whose fathers smoke displayed higher odds of smoking (aOR = 1.35, CI = 1.04,1.76) compared to individuals with non-smoking parents. Additionally, those whose closest friends smoke showed remarkably higher odds of smoking (aOR = 2.87,CI = 2.37, 3.48) compared to those without such influence. Conclusion This study underscores the significant impact of exposure to both anti-tobacco and pro-tobacco media messages and events on smoking behaviour among adolescents in Gambia. However, pro-tobacco messages had a greater influence on smoking prevalence than anti-tobacco messages and events. Understanding these associations is crucial for devising effective public health interventions aimed at reducing tobacco use in this population.